Baitul Mal Wa Tamwil: Legality and Its Potential in Developing the Community's Economy - Khairudin Khairudin (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2022)
This study describes the legality and potential of Baitul Mal Wa Tamwil in developing the community's economy. This study is a literature review, which uses a sociological juridical approach. The data collection technique used in this study is the documentation technique. Meanwhile, the analytical technique used by researchers in this research is qualitative descriptive, where the author will first explain the data related to Baitul Maal Wa Tamwil (BMT) in detail and then carry out an inductive analysis to find out the legality and potential of baitul maal wa tamwil. (BMT) in developing the community's economy. After conducting in-depth research two conclusions were found: first, baitul Maal Wa Tamwil currently uses the cooperative law as its legal basis. Second, the potential for community economic development through Baitul maal wa tamwil is extraordinary because of the financing products (mudhorabah/profit sharing) carried out by baitul mal wa tamwil.